At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the equation, [tex]\(\log \left(q^2 + 7q\right) = \log 18\)[/tex], follow these steps:
1. Remove the logarithms:
Since we have [tex]\(\log A = \log B\)[/tex], we can equate the arguments:
[tex]\[ q^2 + 7q = 18 \][/tex]
2. Set up the quadratic equation:
Rewrite the equation in standard form:
[tex]\[ q^2 + 7q - 18 = 0 \][/tex]
3. Solve the quadratic equation:
To solve [tex]\(q^2 + 7q - 18 = 0\)[/tex], factorize or use the quadratic formula [tex]\(q = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] where [tex]\(a = 1\)[/tex], [tex]\(b = 7\)[/tex], and [tex]\(c = -18\)[/tex].
4. Find the solutions:
Solve the quadratic equation by factoring:
[tex]\[ (q + 9)(q - 2) = 0 \][/tex]
Set each factor to zero and solve for [tex]\(q\)[/tex]:
[tex]\[ q + 9 = 0 \quad \Rightarrow \quad q = -9 \][/tex]
[tex]\[ q - 2 = 0 \quad \Rightarrow \quad q = 2 \][/tex]
5. Verify the solutions:
Substitute [tex]\(q = -9\)[/tex] and [tex]\(q = 2\)[/tex] back into the original argument [tex]\(q^2 + 7q\)[/tex] to ensure the solutions are valid:
[tex]\[ \log((-9)^2 + 7(-9)) = \log(81 - 63) = \log(18) \quad \text{(valid)} \][/tex]
[tex]\[ \log(2^2 + 7 \cdot 2) = \log(4 + 14) = \log(18) \quad \text{(valid)} \][/tex]
Both solutions are valid. Thus, the exact solution set is:
[tex]\[ \boxed{-9, 2} \][/tex]
1. Remove the logarithms:
Since we have [tex]\(\log A = \log B\)[/tex], we can equate the arguments:
[tex]\[ q^2 + 7q = 18 \][/tex]
2. Set up the quadratic equation:
Rewrite the equation in standard form:
[tex]\[ q^2 + 7q - 18 = 0 \][/tex]
3. Solve the quadratic equation:
To solve [tex]\(q^2 + 7q - 18 = 0\)[/tex], factorize or use the quadratic formula [tex]\(q = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex] where [tex]\(a = 1\)[/tex], [tex]\(b = 7\)[/tex], and [tex]\(c = -18\)[/tex].
4. Find the solutions:
Solve the quadratic equation by factoring:
[tex]\[ (q + 9)(q - 2) = 0 \][/tex]
Set each factor to zero and solve for [tex]\(q\)[/tex]:
[tex]\[ q + 9 = 0 \quad \Rightarrow \quad q = -9 \][/tex]
[tex]\[ q - 2 = 0 \quad \Rightarrow \quad q = 2 \][/tex]
5. Verify the solutions:
Substitute [tex]\(q = -9\)[/tex] and [tex]\(q = 2\)[/tex] back into the original argument [tex]\(q^2 + 7q\)[/tex] to ensure the solutions are valid:
[tex]\[ \log((-9)^2 + 7(-9)) = \log(81 - 63) = \log(18) \quad \text{(valid)} \][/tex]
[tex]\[ \log(2^2 + 7 \cdot 2) = \log(4 + 14) = \log(18) \quad \text{(valid)} \][/tex]
Both solutions are valid. Thus, the exact solution set is:
[tex]\[ \boxed{-9, 2} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.